Effect of inhibitors and fertigation strategies on GHG emissions, NO fluxes and yield in irrigated maize - Guardia, Guillermo; Cangani, Max T. [UNESP]; Andreu, Gemma; Sanz-Cobena, Alberto; García-Marco, Sonia; Álvarez, José Manuel; Recio-Huetos, Jaime; Vallejo, Antonio (Elsevier, 2017)
Abating large losses of nitrogen (N) oxides while maintaining or enhancing crop yield is a major goal in irrigated maize (Zea mays L) cropping areas. During two consecutive campaigns, the new nitrification inhibitor 2-(3,4-dimethyl-1H-pyrazol-1-yl) succinic acid isomeric mixture (DMPSA) applied with calcium ammonium nitrate (CAN) and the same fertilizer applied by drip-fertigation without the inhibitor, were evaluated and compared with CAN broadcast to the surface and irrigated with sprinklers. Concurrently, urea-based treatments such as urea-fertigation and the broadcast application of urea combined with sprinkler irrigation, with or without the urease inhibitor N-butyl thiophosphorictriamide (NBPT), were also assessed. Nitrous oxide (N2O) and nitric oxide (NO) fluxes, grain and biomass yield and yield-scaled N2O emissions of the different treatments were compared. Additionally, methane (CH4) and carbon dioxide (CO2) fluxes were measured. On average, fertigation treatments led to a mitigation of N2O emissions with respect to sprinkler irrigation by 80% and 78% for CAN and urea, respectively. With regards to inhibitor-based strategies, the use of DMPSA and NBPT reduced N2O losses by 58% and 51%, respectively, considering the average of both maize cropping seasons. Since no differences in grain yield were observed between fertilized treatments, DMPSA and fertigation treatments gave the lowest values of yield-scaled N2O emissions, leading to reductions of 63%, 71% and 78% for CAN with DMPSA, urea-fertigation and CAN-fertigation, respectively, with respect to conventional management strategies (surface broadcast application and sprinkler irrigation). Low NO emissions during the first campaign masked differences between treatments, whereas during the second season, NO losses significantly decreased in the following order: conventional treatments > inhibitors > fertigation. Comparing conventional management practices, CAN significantly decreased emissions of N oxides compared with urea, but this effect was only observed in the second maize cropping season. The moisture distribution pattern in drip plots (dry and wet areas) caused a reduction of CH4 sink (only in one of the two seasons) and respiration fluxes, in comparison to sprinkler. This study shows that the use of the new nitrification inhibitor DMPSA and drip-fertigation should be promoted in irrigated maize agro-ecosystems, in order to mitigate emissions of N oxides without penalizing grain yield and leading to similar or enhanced biomass production.
Keywords: Fertigation; GHG emission; Nitric oxide emission; Nitrification inhibitor DMPSA; Urease inhibitor NBPT